Pengaruh komposisi MnFe2O4 terhadap sifat magnetik nanokomposit MnFe2O4 / PVDF yang di preparasi dengan metode spin coating (The effect of the MnFe2O4 composition on the magnetic properties of the MnFe2O4 / PVDF nanocomposites prepared by the spin coating method) - Romizah Marta; Yenni Darvina; - Ramli; - Desnita (PILLAR OF PHYSICS, 2020)
Now is the age of the "Internet of things", where physical devices are able to exchange information between information sources connected to the system. To build a system, it takes a components device which in the  manufacturing process is made into Nanocomposites. In this research, the materials used as Nanocomposites are Manganese ferrite (MnFe2O4) and Polyvinilidene Flouride (PVDF). Then the method used is the Spin Coating. The Spin Coating Method is used to grow a thin layer of MnFe2O4 / PVDF Nanocomposites. In the process of making Nanocomposites, Manganese and Iron are used as precursors. In this research, researcher used five variations of the composition of MnFe2O4 / PVDF Nanocomposites, namely 25% : 75%, 33.33%: 66.67%, 50% : 50%, 66.67%: 33.33% and 75%: 25%. There are three characterization tools used in this research namely XRD, FTIR and VSM. The results of XRD characterization as supporting data in this research show each peak has a different angle of 2Ө, intensity, FWHM value and Miller Index. Crystal form of PVDF is Monoclinic and Crystal form of MnFe2O4 is Cubic. The results of FTIR characterization as supporting data found two functional groups, namely Fe-O and CH2. For Fe-O is the MnFe2O4 Function Group, and CH2 is the PVDF Function Group or (C2H2F2)n. The results of the characterization of VSM as the results of the study show the relationship between the variation of the composition of the MnFe2O4 / PVDF Nanocomposites with Saturation Magnetization which tends to decrease which is worth 2.07 at 25% : 75% composition, 1.11 at 33.33% : 66.67% composition, 1 at 50% : 50% composition, 1.54 at 66.67% : 33.33% composition and 1.09 at 75%: 25% composition. The same result also occurs in the relationship of composition variation with Remanent Magnetization, which is worth 0.37 at 25% : 75% composition, 0.35 at 33.33% : 66.67%, 0.47 at 50% : 50% composition, 0.31 at 66.67% : 33.33% composition, 0.25 at 75% : 25% composition. Furthermore, the results of the relationship of variations in the composition of MnFe2O4 / PVDF nanocomposite with Coercivity is high low Coercivity values. This shows the change in nature from Hard Magnetic to Soft Magnetic. The value of Coercivity is 297.08 at 25% : 75% composition, 144.96 at 33.33%: 66.67% composition, 274.05 at 50% : 50% composition, 300.53 at 66.67% : 33.33% composition and 196.57 at 75% : 25% composition.